Dinamika Budaya Kerja dan Motivasi Guru dalam Meningkatkan Kinerja di SMA Negeri 1 Indralaya - Sarimawati (UNISAN JURNAL, 2024)
This research aims to analyze the relationship between the dynamics of work culture and teacher motivation in improving performance at SMA Negeri 1 Indralaya. The research method used is a descriptive analytical method with a quantitative approach. Data was collected through a questionnaire distributed to 100 teacher respondents at SMA Negeri 1 Indralaya. The results of the analysis show that there is a significant relationship between the dynamics of work culture and teacher motivation in improving performance. A positive work culture, including good communication, teamwork, and recognition of achievements, has a positive impact on teacher motivation. Teachers' high motivation is reflected in their dedication to the profession, desire to continue learning and developing, and active involvement in school activities. These findings provide important implications for school administrators to improve the quality of work culture and strengthen teacher motivation as an effort to improve school performance. This research also provides theoretical contributions to the understanding of the factors that influence teacher performance and their relevance to the organizational cultural context in high schools. Future research can further explore effective interventions to improve work culture dynamics and strengthen teacher motivation to achieve better school performance.